1987
DOI: 10.1016/s0735-1097(87)80207-3
|View full text |Cite
|
Sign up to set email alerts
|

Disopyramide-pyridostigmine interaction: Selective reversal of anticholinergic symptoms with preservation of antiarrhythmic effect

Abstract: This double-blind, randomized, placebo crossover study was used to evaluate the effects of a cholinesterase inhibitor--slow-release pyridostigmine (180 mg orally every 12 hours)--on the anticholinergic and antiarrhythmic properties of disopyramide. Quantitative side effects questionnaire scores were used to guide disopyramide administration in 20 men with ventricular tachycardia. Disopyramide was given to each patient both with placebo and with active pyridostigmine. The maximal administered dose for each regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This allows continuation of adequate disopyramide dosing. 15 Patients who had no symptom improvement, or who experienced drug side effects were referred for surgical septal myectomy, unless they had significant medical comorbidity or refused surgery. 3 Selected patients were referred for surgical septal myectomy without an intervening disopyramide trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows continuation of adequate disopyramide dosing. 15 Patients who had no symptom improvement, or who experienced drug side effects were referred for surgical septal myectomy, unless they had significant medical comorbidity or refused surgery. 3 Selected patients were referred for surgical septal myectomy without an intervening disopyramide trial.…”
Section: Methodsmentioning
confidence: 99%
“…15 Half of our patients received pyridostigmine timespan at least temporarily. The safety of the combination in obstructive HCM is shown in the present study.…”
Section: Disopyramidementioning
confidence: 99%
“…Other drugs, such as the anticholinesterases distigimine [96] and pyridostigmine [84], have also been used in managing xerostomia, although to a much lesser extent.…”
Section: Drug Therapymentioning
confidence: 99%
“…Pyridostigmine has been traditionally used for the treatment of myasthenia gravis due to its action on the motor plate in skeletal muscle (11). In addition, it has been shown to counteract the adverse anti-cholinergic effects of disopyramide, such as decreased baseline saliva and tear production (12). We have previously shown that short-term administration of pyridostigmine may be also potentially useful for cardiovascular protection since in healthy individuals and patients with cardiovascular diseases it results in beneficial effects on markers of cardiovascular risk and dysfunction (8,(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%